The use of green tea, spirulina and garcinia cambogia as herbal medicines associated with the treatment of localized fat (Research, Society and Development, 2023)
The World Health Organization (WHO) recognizes that obesity is currently a growing global problem, men and women of different age groups suffer from the disease, treating obesity and localized fat requires combining multidisciplinary treatment, with changes in eating habits and physical activity, as there are a lot of side effects when using pharmacological treatment, there has been increased interest in alternative therapies such as herbal medicines, they are natural products obtained from medicinal plants, the therapeutic properties of herbal medicines are used as a cure and prevention treatment for some diseases , among the herbal medicines known for reducing localized fat, we can highlight green tea, spirulina and garcinia cambogia, green tea has varied benefits, and can be used for both fat burning, stress, used as a thermogenic, it has in its composition catechins, caffeine in abundant quantity, spirulina is used for various situations such as combating free radicals, treating osteoporosis, appetite suppressant for those looking to lose weight, preventing premature aging, making it a great dietary supplement , promoting the immune system in its composition several vitamins are part of its arsenal with many vitamins, garcinia gummi-gutta is very good for the treatment of gastrointestinal disorders, a strong ally against diabetes, consequently reduces the production of insulin, resulting from the above an analysis of the components such as quantity of consumption and contraindications were compared with the intention of verifying which is the best herbal medicine to aid in the treatment of fat burning. Garcinia, this dried fruit, can be used for decoction, that is, making teas. This herbal medicine is composed of hydroxycitric acid, which has an action on adipose tissue to reduce body fat, this occurs due to the increase in lipid oxidation, its daily dose cannot exceed 2g, as there are reports in various literature of people who have suffered injuries liver damage due to excessive use of garcinia cambogia and the adverse effects caused may include headaches, nausea, upper respiratory tract symptoms and gastrointestinal symptoms. Green tea helps improve the intestine, but care must be taken with the dose, as there are reports in the literature that when ingested in excess it can be hepatoxic, in addition to being contraindicated for patients with hypersensitivity to the substance it contains caffeine, a study on anti-obesity treatment with natural methods mentions that there is an importance in modulating the microbiota to achieve good intestinal health of the patient. Spirulina is contraindicated for those with phenylketonuria, autoimmune diseases, pregnant and lactating women, although in rare cases, side effects include headaches, nausea, diarrhea and vomiting. As all herbal medicines generate benefits, they help in the weight loss process, but depending on the contraindications and availability on the market, spirulina is the most suitable for short, medium and long term consumption, easy to find in the same proportion as green tea , but with fewer contraindications compared to it, is available all over the world and its cost-benefit ratio is not high.